Decision Processes of a Suicide Bomber – Integrating Economics and Psychology - Karen Pittel; Dirk T. G. Rübbelke (ETH Zurich, CER-ETH - Center of Economic Research, 2009)
This paper provides a theoretical analysis regarding the rationality of suicide attacks from an economist's point of view. It is argued that although a terrorist gives up future utility from consumption by committing a suicide attack, this loss can be overcompensated by the utility he derives from the attack. Some individual cases of suicide bombers are presented in order to elucidate the diversity of motivations behind the attacks. We derive conditions under which a rational agent might decide to become a suicide bomber – or to announce the attack and defect later. The paper shows why the decision to commit a suicide attack can be time-inconsistent and what mechanisms might prevent time-inconsistency. Integrating the psychological concepts of cognitive dissonance and terror management theory into our economic analysis, we demonstrate why – although predicted by standard economic theory – defection is a phenomenon rarely observed. We finally present some policy implications. In the light of our analysis, policies that focus on material well-being seem less promising than policies that address non-monetary benefits of suicide attacks. The paper concentrates on two policy strategies: offering alternatives – with respect to the aims of terrorism as well as the means to attain them – and reducing the information bias – with respect to the availability as well as the access to information.
Keywords: D74; D69; 330; terrorism; discounting; rationality; time-consistency; Terrorismus; Rationalität; Intertemporale Entscheidung; Entscheidung unter Unsicherheit; Theorie